2016
DOI: 10.1371/journal.pone.0161926
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma diversum Genome Provides New Insights about the Interaction of the Surface Molecules of This Bacterium with the Host

Abstract: Whole genome sequencing and analyses of Ureaplasma diversum ATCC 49782 was undertaken as a step towards understanding U. diversum biology and pathogenicity. The complete genome showed 973,501 bp in a single circular chromosome, with 28.2% of G+C content. A total of 782 coding DNA sequences (CDSs), and 6 rRNA and 32 tRNA genes were predicted and annotated. The metabolic pathways are identical to other human ureaplasmas, including the production of ATP via hydrolysis of the urea. Genes related to pathogenicity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(65 citation statements)
references
References 86 publications
0
60
0
5
Order By: Relevance
“…lipopolysacchride) induce the activation of caspase-1 and release of IL-1β in the chorioamniotic membranes 35, 37, 117 and that Ureaplasma species (genital mycoplasmas are the most common microorganisms found in women with IAI 12, 16, 118123 ) are capable of activating the inflammasome pathway in murine macrophages. 124 Together, these findings indicate that the inflammasome is involved in the mechanisms that lead to microbial-associated preterm labor and birth.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…lipopolysacchride) induce the activation of caspase-1 and release of IL-1β in the chorioamniotic membranes 35, 37, 117 and that Ureaplasma species (genital mycoplasmas are the most common microorganisms found in women with IAI 12, 16, 118123 ) are capable of activating the inflammasome pathway in murine macrophages. 124 Together, these findings indicate that the inflammasome is involved in the mechanisms that lead to microbial-associated preterm labor and birth.…”
Section: Discussionmentioning
confidence: 91%
“…These results are consistent with previous studies, which demonstrated that amniotic fluid concentrations of caspase-1 33 (the predominant inflammasomeactivated caspase 46 ), IL-1β, 26 and IL-18 106 35,37,117 and that Ureaplasma species (genital mycoplasmas are the most common microorganisms found in women with IAI 12,16,[118][119][120][121][122][123] ) are capable of activating the inflammasome pathway in murine macrophages. 124 Together, these findings indicate that the inflammasome is involved in the mechanisms that lead to microbialassociated preterm labor and birth.…”
Section: Inflammasome Activation In Spontaneous Preterm Labor With mentioning
confidence: 90%
“…ASC/caspase-1 complexes), compared to those without this placental lesion [53,54]. Furthermore, genital mycoplasmas, the most common microorganisms found in women with clinical chorioamnionitis at term and intra-amniotic infection [40,85,108], are capable of activating the inflammasome pathway in murine macrophages [109]. Together, these findings indicate that the inflammasome is involved in the mechanisms that lead to microbial-associated intra-amniotic inflammation in women with clinical chorioamnionitis at term.…”
Section: In Vivo Evidence Of Inflammasome Activation In Clinical Chormentioning
confidence: 88%
“…NF-κB and AP-1 regulate important genes associated with inflammation in infection processes ( Garcia et al, 1998 ; Rawadi et al, 1999 ). Accordingly, the recent genome analyses of U. diversum revealed a large number of genes encoding membrane-associated lipoproteins, as well as urease, hemolysin, phospholipase and glycosyltransferase (associated with capsule synthesis) enzymes ( Marques et al, 2015 , 2016 ). These lipoproteins, however, have never been separately analyzed for their host immune system stimulation.…”
Section: Introductionmentioning
confidence: 99%